Correlations of the Circadian Rhythmicity of Blood Pressure With Erectile Dysfunction - Ajar Koçak; Cem Şenol; Onur Yıldırım; Bilgesu Arıkan Ergün (The Journal of Clinical Hypertension)
ABSTRACT Erectile dysfunction (ED) and cardiovascular diseases (CVD) share common pathophysiological mechanisms. This study aimed to assess the relationship between ED and its severity with the risk of developing CVD by analyzing changes in the circadian blood pressure (BP) rhythm. In the study, 24‐h BP levels of 192 (94 with ED and 98 controls) participants with no history of CVD were evaluated using an ambulatory blood pressure monitoring (ABPM) device. The International Index of Erectile Function (IIEF) questionnaire was used to assess the ED severity in the study group. ABPM measurements revealed higher BP values among the ED group. The nondipper pattern was significantly more frequent in the ED group compared to the controls (56.2% vs. 77.1%, p < 0.01). Blood pressure variability parameters, including systolic standard deviation (SD) and average real variability (ARV), were notably higher in the ED group (16.3 ± 3.9 vs. 14.6 ± 4.3, p < 0.01 and 13.39 ± 7.24 vs. 11.5 ± 2.1, p < 0.01, respectively). Furthermore, parameters reflecting arterial stiffness including pulse pressure index (PPI) and ambulatory arterial stiffness index (AASI) were higher in the ED group (0.81 ± 0.33 vs. 0.73 ± 0.18, p = 0.03 and 0.71 ± 0.09 vs. 0.59 ± 0.17, p = 0.014, respectively). Both AASI and ARV were significantly correlated with the severity of ED. This study suggests a significant association between ED severity and altered blood pressure patterns which in part explains the increased risk of CVD among individuals with ED.